Hepatitis E virus infection increases the risk of diabetes and severity of liver disease in patients with chronic hepatitis C virus infection (Clinics, 2021)
OBJECTIVES: Co-infection with hepatitis A or B viruses may aggravate liver injury in patients infected with hepatitis C virus (HCV). However, few studies have assessed co-infection with hepatitis E virus (HEV) and HCV. Therefore, this study aimed to assess the prevalence and impact of HEV infection among Brazilian patients with chronic HCV infection.METHODS: This observational study included adult patients with chronic HCV infection who were naive to antiviral therapy from January 2013 to March 2016. A total of 181 patients were enrolled, and HEV serology and PCR were performed for all patients.RESULTS: Seropositivity for anti-HEV IgG was detected in 22 (12.0%) patients and anti-HEV immunoglobulin M in 3 (1.6%). HEV RNA showed inconclusive results in nine (4.9%) patients and was undetectable in the remaining patients. HEV serology positive patients had more severe liver disease, characterized by liver fibrosis ≥3 versus ≤2 (p<0.001), Aspartate Aminotransferase-to-Platelet Ratio Index of ≥1.45 (p=0.003), and Fibrosis-4 score of ≥3.25 (p=0.001). Additionally, the odds of HEV-positive patients developing diabetes mellitus were 3.65 (95% CI 1.40-9.52) times the corresponding odds of HEV-negative patients. A case-control-based histological analysis (n=11 HEV-HCV-positive patients and n=22 HCV-positive patients) showed no significant differences between the groups.CONCLUSIONS: This prevalence is higher than that reported in previous studies of the general population in Brazil. Thus, HEV infection may influence the severity of liver disease and may represent an additional risk of developing diabetes mellitus in patients with HCV infection.